Operational Feasibility Review of the Well Design Standardization for Offshore Drilling Operations Optimization - Ridha, Syahrir; Yakob, Razak; Anis A Rahman, Afizza; Mohd Saaid, Ismail (International Journal of Engineering and Technology, 2018)
Well cost is a major component in a field developmentâ€™s project cost.Â Various initiatives have been engineered and implemented to optimize the well design and operation to reduce the well cost.Â One of the initiatives that can be considered is the Well Design Standardization (WDS).Â It is a concept of having a set of standardized well designs with limited variation.Â The main objectives of implementing WDS are reduction to the overall well cost through economies of scale and equipment surplus consolidation.Â It is conceptually logical and simple.Â However, the concept may not be feasible in all operational conditions.Â This paper shall cover the WDS concept, implementation benefits, implementation challenges and mechanisms to make the concept operationally feasible.Â The objectives of this paper are to introduce the WDS concept, and provide some considerations that can benefit the planning and implementation of WDS in drilling projects.Â WDS is an opportunity that needs to be considered in an operation, because significant cost saving can be achieved if the right mechanisms were applied.Â Â